2008
DOI: 10.5194/acp-8-3705-2008
|View full text |Cite
|
Sign up to set email alerts
|

Validation of aerosol and cloud layer structures from the space-borne lidar CALIOP using a ground-based lidar in Seoul, Korea

Abstract: Abstract. We present initial validation results of the space-borne lidar CALIOP onboard CALIPSO satellite using coincidental observations from a ground-based lidar in Seoul National University (SNU), Seoul, Korea (37.46 • N, 126.95 • E). We analyze six selected cases between September 2006 and February 2007, including 3 daytime and 3 night-time observations and covering different types of clear and cloudy atmospheric conditions. Apparent scattering ratios calculated from the two lidar measurements of total a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
104
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(111 citation statements)
references
References 21 publications
2
104
0
2
Order By: Relevance
“…In addition to aircraft studies previously discussed , ground based lidars have also offered an assessment of CALIOP attenuated backscatter profiles. Kim et al (2008) qualitatively show good agreement between an elastic backscatter lidar and CALIOP attenuated backscatter. In another study, Mamouri et al, 2009 used a ground based Raman lidar for nighttime validation and an elastic backscatter lidar for daytime validation of the CALIOP 532 nm total attenuated backscatter.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In addition to aircraft studies previously discussed , ground based lidars have also offered an assessment of CALIOP attenuated backscatter profiles. Kim et al (2008) qualitatively show good agreement between an elastic backscatter lidar and CALIOP attenuated backscatter. In another study, Mamouri et al, 2009 used a ground based Raman lidar for nighttime validation and an elastic backscatter lidar for daytime validation of the CALIOP 532 nm total attenuated backscatter.…”
Section: Discussionmentioning
confidence: 65%
“…Since the launch of CALIPSO, several studies have been conducted validating the CALIOP data products (Mona et al, 2009;Mamouri et al, 2009;Kim et al, 2008). Some promising results were also published by McGill et al (2007) qualitatively comparing measurements from CALIOP to the Cloud Profiling Lidar (CPL) deployed on the ER-2 aircraft.…”
Section: Introductionmentioning
confidence: 90%
“…Huang et al, 2008), the height-resolved global distribution of dust aerosols (D. , long-distance dust aerosol vertical distribution over Shanghai, China, (Chen et al, 2008), the Saharan dust outflow (Generoso et al, 2008), and Taklamakan dust aerosol radiative heating ). Kim et al (2008) confirmed that the CALIPSO algorithms discriminate clouds and aerosols and detect the layer top and base altitudes reliably by comparing CALIOP and ground-based lidar data at a site far from the dust source, in Seoul, Korea. However, as pointed out by Z.…”
Section: Introductionmentioning
confidence: 59%
“…Synergy of these nadir-viewing sensors allows for a complete representation of physical cirrus cloud properties. The high quality of processed CALIPSO data products has been demonstrated through validation campaigns Winker et al, 2007;Vaughan et al, 2008;Kahn et al, 2008;Kim et al, 2008).…”
Section: Introductionmentioning
confidence: 99%